Partially etched Bi2O2CO3 by metal chloride for enhanced reactive oxygen species generation : a tale of two strategies - Ding, Penghui (2021)
Light-mediated reactive oxygen species generation with water and oxygen is generally regarded as a mild and efficient way for organic pollutants removal. However, it is highly difficult but desirable to construct a photochemical system with increased reactive oxygen species production. Herein, by using Bi2O2CO3 as a prototype, we devise a simple metal chloride-involved etching method to achieve better light absorption and charge carriers separation in a wide-band-gap semiconductor, thus giving rise to improved molecular oxygen activation. The improved photoinduced reactive oxygen species production is further verified by excellent photocatalytic degradation ability of RhB, TC and BPA under visible and ultraviolet light illumination. In addition, the metal chloride-induced strategies—heterojunction formation and cation doping—significantly affect the dynamics and transfer of carriers, which are advantageous to manipulate one-/two-electron pathway for producing reactive oxygen species.